Peasant women of Characato - Sara-Lafosse, Violeta (1985)
Characato is a district of the province of Arequipa, which bears this denomination because it is the administrative political delimitation in which the city of the same name is located. Arequipa, with a population of half a million inhabitants, is the second largest city in the country. Characato, with an area of ​​657.55 hectares and 2,695 inhabitants, is located southeast of the city and its populated center is 30 kilometers from it. It is located at an altitude of about 2,400 meters, so its climate is mild throughout the year. The population of Characato has easy access to the city. A partially paved road connects the district with the capital of the department.